2008
DOI: 10.1158/1535-7163.mct-08-0629
|View full text |Cite
|
Sign up to set email alerts
|

Loss of prostaglandin D2 synthase: a key molecular event in the transition of a low-grade astrocytoma to an anaplastic astrocytoma

Abstract: Reduction in the mRNA and protein expression of lipocalin-like prostaglandin D 2 (PGD 2 ) synthase (PGDS), the main arachidonic acid metabolite produced in neurons and glial cells of the central nervous system, is a significant biological event involved in the malignant progression of astrocytomas and is predictive of poor survival. In vitro, the addition of the main PGDS metabolite, PGD 2 , to A172 glioblastoma cells devoid of PGDS resulted in antiproliferative activity and cell death. In vitro PGD 2 substitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…PGD2 is synthesized by hematopoietic PGD synthase or PTGDS. Both PTGDS and TBXAS1 are regulated by DNA methylation [28,29]. We found the hypomethylation and upregulation of both enzymes by 5-AZA in different cells and mice, which agrees with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…PGD2 is synthesized by hematopoietic PGD synthase or PTGDS. Both PTGDS and TBXAS1 are regulated by DNA methylation [28,29]. We found the hypomethylation and upregulation of both enzymes by 5-AZA in different cells and mice, which agrees with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…This might be surprising insofar as PGD 2 and its final metabolite 15deoxyD 12-14 PGJ 2 are implicated in the onset of apoptosis, through the activation of DP receptors or of PPARg 26 or of other targets. 19 Payne et al 35 also reported that L-PGDS loss was observed during transition from low grade to higher grade astrocytomas and was correlated to a poorer survival. However, our results demonstrate that PGD 2 is not an absolute antiapoptotic compound, but rather a competitive inhibitor of PGE 2 in Bax activation, as it does not preclude the Bid-induced activation of Bax.…”
Section: Discussionmentioning
confidence: 97%
“…Reduction of ß-trace protein is a significant biological event involved in the malignant progression of astrocytoma and is predictive of poor survival (35). Significant reduction in cell proliferation and viability in the A172 glioblastoma cell line was found when PGD 2 was exogenously supplied.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%